Orphans of the Mexican drug war: insights on a public health challenge - Camacho, Salvador; Horstick, Olaf; Sax, Sylvia (Revista panamericana de salud pública, 2014)
OBJECTIVE: To describe how the Government of Mexico and other direct stakeholders perceive children orphaned by the drug war; to determine the current measures addressing this as a public health problem; and to compare these measures to international frameworks so that relevant recommendations can be identified. METHODS: This was an exploratory, descriptive case study using qualitative methods. Semi-structured interviews were performed with key informants at the federal, state, and municipal government levels in Mexico, as well as non-governmental organizations, and other institutes working with orphans. Participants were identified with a purposive snowball sample. RESULTS: No official definition of "orphan" was identified; nor was there a shared perception among the key informants of what constitutes being an orphan. An official, collective definition is important because it modifies the quantity of children categorized as such within the target population. Although most of the interviewees perceive that the number of orphans and vulnerable children (OVC) has increased in the last 6 years, they acknowledged there is no reliable data to prove it. The increase, they believe, is due not to the drug war, but to a loss of family cohesion. Stakeholders recommend improving public policies, currently identified as the most difficult barrier to overcome due to a perceived inability to modify existing laws. However, the General Law for Victims was recently passed by the Government of Mexico and addresses many of the challenges identified. CONCLUSIONS: When compared to the international frameworks, there are three major issues in Mexico's current situation: coordination among and within stakeholders; emphasis on using community solutions; and putting in place preventive programs. For two of these problems, the General Law of Victims offers solutions.